SOSIALISASI DAN PENDAMPINGAN PEMANFAATAN LIMBAH JAGUNG SEBAGAI PRODUK UNGGULAN DESA KEDUKBEMBEM, KECAMATAN MANTUP, LAMONGAN - Puji Andayani; Habib Mudhofir Hariri; Afninda Aryuni Widyanti; Nurul Fadhillah Achmad; Nur Efita; Putu Setia; Febri Nur Anggraeni; Novi Putriyani Puspita; Bagastya Asyhari (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Kedukbembem village is located in Mantup sub-district, Lamongan district. Corn is one of the most important commodities in Kedukbembem village. People have been selling corn in the form of pritilan corn. Corn hair and cob eventually become waste that cannot be utilized. Through the community service program, UISI provides product innovations from corn waste to corn cob briquettes and corn hair decoction. The corn hair innovation product is further socialized, and product development assistance is provided to the public. This product is expected to be the flagship product of Kedukbembem village. The community will be given socialization on making corn cob briquettes and corn hair tea. Assistance to the Kedukbembem village community includes help in making packaging, labeling, and submitting PIRT. Through this service, it is hoped that it can provide insight into the community, increase the villagers' income, and increase the commodity of Kedukbembem village. --- Desa Kedukbembem berada di Kecamatan Mantup Kabupaten Lamongan. Jagung merupakan salah satu komoditi terbesar desa Kedukbembem. Masyarakat selama ini menjual jagung dalam bentuk jagung pritilan. Rambut jagung dan bonggolnya akhirnya menjadi limbah yang tidak dapat dimanfaatkan. Melalui program pengabdian masyarakat UISI memberikan inovasi produk dari limbah jagung menjadi briket bonggol jagung dan teh rambut jagung. Produk inovasi rambut jagung selanjutnya disosialisasikan dan dilakukan pendampingan pengembangan produk kepada masyarakat. Produk ini diharapkan dapat menjadi produk unggulan desa Kedukbembem. Masyarakat akan diberikan sosialisasi pembuatan briket bonggol jagung dan teh rambut jagung. Pendampingan kepada masyarakat desa Kedukbembem meliputi pendampingan dalam pembuatan kemasan, labeling, dan pengajuan PIRT.  Melalui pengabdian ini diharapkan dapat memberikan insight kepada masyarakat dan meningkatkan penghasilan warga desa, dan menambah komoditi desa Kedukbembem.